2004
DOI: 10.1677/joe.0.1800479
|View full text |Cite
|
Sign up to set email alerts
|

The oncostatin M receptor/gp130 ligand murine oncostatin M induces apoptosis in adrenocortical Y-1 tumor cells

Abstract: The effects of murine oncostatin M (mOSM) are specifically mediated by the heterodimeric oncostatin M receptor (OSMR)/gp130 receptor complex. In the current study we demonstrate that murine adrenocortical Y-1 tumor cells express the OSMR/gp130 complex. Incubation of Y-1 cells with 1 and 10 ng/ml mOSM induces cell death due to specific induction of apoptosis. Western blot analysis of Y-1 cells incubated with mOSM for 24 h revealed caspase-3 cleavage and poly(ADP-ribase) polymerase (PARP) cleavage. In a prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Like the EGFR, it has established roles in promoting cancer and tumor formation in malignant prostate [42], lung, head and neck, and cervical [43] tissue. In addition, OSM has been shown in some cells to induce apoptosis [4446]. Thus, stimulation of the OSM receptor was a logical candidate for testing our hypothesis that STAT3 is a mediator apoptosis, independent of EGFR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Like the EGFR, it has established roles in promoting cancer and tumor formation in malignant prostate [42], lung, head and neck, and cervical [43] tissue. In addition, OSM has been shown in some cells to induce apoptosis [4446]. Thus, stimulation of the OSM receptor was a logical candidate for testing our hypothesis that STAT3 is a mediator apoptosis, independent of EGFR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as described recently [26,27]. Briefly, cells were lysed in 500 µl lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies focused on the effects of OSM on apoptosis, and the conclusions were opposite according to the model. A recent study has shown that OSM induces apoptosis in adrenocortical Y-1 tumor cell line, implicating the JAK-STAT pathway and caspase-3 activation (Auernhammer et al, 2004). On the other hand, OSM was able to protect MG63 osteosarcoma cells from apoptosis induced by an anti-Fas antibody by preventing the loss of Bcl-2 protein (Jilka et al, 1998).…”
Section: Introductionmentioning
confidence: 98%